2017
DOI: 10.1016/s1474-4422(16)30328-3
|View full text |Cite
|
Sign up to set email alerts
|

Clinical variables and biomarkers in prediction of cognitive impairment in patients with newly diagnosed Parkinson's disease: a cohort study

Abstract: Summary Background Parkinson’s disease is associated with an increased incidence of cognitive impairment and dementia. Predicting who is at risk of cognitive decline early in the disease course has implications for clinical prognosis and for stratification of participants in clinical trials. We assessed the use of clinical information and biomarkers as predictive factors for cognitive decline in patients with newly diagnosed Parkinson’s disease. Methods The Parkinson’s Progression Markers Initiative (PPMI) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
320
2
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 330 publications
(360 citation statements)
references
References 36 publications
17
320
2
4
Order By: Relevance
“…Regardless of the site of autonomic dysfunction, this association might suggest a more severe clinical phenotype of the disease in PD with ICB. Dysautonomia may predict worse disease progression in early PD,32 and lower MoCA score and RBD at the time of PD diagnosis have been found as predictive factors of mild cognitive impairment 33…”
Section: Discussionmentioning
confidence: 98%
“…Regardless of the site of autonomic dysfunction, this association might suggest a more severe clinical phenotype of the disease in PD with ICB. Dysautonomia may predict worse disease progression in early PD,32 and lower MoCA score and RBD at the time of PD diagnosis have been found as predictive factors of mild cognitive impairment 33…”
Section: Discussionmentioning
confidence: 98%
“…Most of these longitudinal evaluations followed early, initially untreated patients. Among those with normal cognition at baseline, one-year PD-MCI incidence in this population has been estimated to be 10% 34 , rising to 20-30% over subsequent years 32, 34, 35, 46 . These rates are not reflective, however, of the proportion developing cognitive impairment, as they exclude those participants transitioning to dementia.…”
Section: Epidemiology Of Pd-mcimentioning
confidence: 99%
“…In particular, poorer performance on language, short-term recall and working memory tasks predicted future development of PD-MCI 47 . Other clinical features that have been associated with a higher risk of developing cognitive impairment include poorer olfactory performance, RBD, depression and greater motor impairment 42, 46 . Biomarkers have been found to have added predictive value, in particular APOE genotype, low CSF Abeta:total tau ratio, and lower putaminal DAT asymmetry 46 .…”
Section: Epidemiology Of Pd-mcimentioning
confidence: 99%
“…A previous study has shown the integration of several key clinical factors as well as genetic risks for PD diagnosis yielded good sensitivity and specificity for PD diagnosis 2. Genetic risk or clinical features based prediction models have been studied in the prediction of PD falls or cognitive impairment 3, 4, 5. Body fluid biomarkers, particularly in the cerebrospinal fluid (CSF), have also been widely tested, including α ‐syn, total and phosphorylated tau (t‐tau and p‐tau), and amyloid beta 1‐42 (A β 1‐42 ), but no single biomarker to date has been capable of accurate diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…Body fluid biomarkers, particularly in the cerebrospinal fluid (CSF), have also been widely tested, including α ‐syn, total and phosphorylated tau (t‐tau and p‐tau), and amyloid beta 1‐42 (A β 1‐42 ), but no single biomarker to date has been capable of accurate diagnosis. In one study, clinical and body fluid markers were combined to successfully predict cognitive impairment in PD 5. However, to our knowledge, no study has used a similar combined model to predict PD diagnosis.…”
Section: Introductionmentioning
confidence: 99%